Interface-induced controllable synthesis of Cu2O nanocubes for electroreduction CO2 to C2H4. (20th May 2019) - Wang, Wenhang; Ning, Hui; Yang, Zhongxue; Feng, Zhaoxuan; Wang, Jialin; Wang, Xiaoshan; Mao, Qinhu; Wu, Wenting; Zhao, Qingshan; Hu, Han; Song, Yan; Wu, Mingbo
Abstract: Electroreduction CO2 to high value-added chemicals is a promising way to mitigate the greenhouse effect while storing the renewable electricity in chemicals. As an important chemical, C2 H4 is a desirable product of CO2 reduction but limited by lacking of efficient and durable catalysts. Herein, we proposed an interface-induced method to prepare Cu2 O nanocubes with controllable morphology and size. Due to the imidazolyl groups connected to the surface of ionic liquid functionalized graphite sheets (ILGS), Cu2 O nanocubes were induced to grow on ILGS to obtain Cu2 O/ILGS composites, where the size of Cu2 O can be controlled by adjusting the concentration of Cu 2+ . Interestingly, as the concentration of Cu 2+ increases from 12.5 mmol/L to 100 mmol/L, the size of Cu2 O nanocubes decreases from 456 nm to 72 nm. As catalyst for CO2 electroreduction in 0.1 M KHCO3 aqueous solution, Cu2 O/ILGS-100 (synthesized under 100 mmol/L CuCl2 ) behaves the best catalysis performance with a high faradic efficiency of C2 H4 (31.1%) and long durability at −1.15 V ( vs. reversible hydrogen electrode). Graphical abstract: Image 1